Pentingnya Pengetahuan Bagi Pelaku Usaha Umkm Samama: Pengaruh Knowledge Management Terhadap Peningkatan Kinerja Umkm Samama - Lailla, Nor; Edward Utama, Rony; Siti Jamilah, Siti Jamilah; Sadtyo Nugroho, Wawan; Tarmizi, M. irfan (Universitas Muhammadiyah Surakarta, 2024)
The aim of this research is to determine knowledge implementing, knowledge creating, and knowledge sharing on the performance of MSMEs in Bojongsari Depok. The method used in this research uses an explanatory research method which is used to find out how big the relationship between variables is. The population in the study was Samama MSMEs in Bojongsari Depok. There were 138 respondents distributed via Google Form, but 49 returned questionnaires. To measure the suitability of the data via the SPSS application. The research results show that knowledge implementing, knowledge creating, and knowledge sharing both partially influence the performance of MSMEs in Bojongsari Depok. The variables knowledge implementing, knowledge creating, and knowledge sharing jointly influence the MSME performance variable by 80.6% while the remaining 19.4% is influenced by other factors